Pitting base rate driven heuristics against conditional reasoning in multivariate contingency assessment - Fiedler, Klaus; Kutzner, Florian (Journal of experimental psychology. Learning, memory, and cognition, 2024)
Contingency assessment is a major module of adaptive cognition and a prominent topic of ecological rationality. Virtually all influential theories assume that contingency estimates between Y and X are inferred from subjective conditional probabilities of focal Y levels given different X levels, p ( Y focal | X different levels ) . Yet, conditional probabilities are cognitively demanding, as Yfocal must be assessed separately for all levels of Xdifferent level. Pseudocontingencies (PCs) afford an alternative mechanism relying on base rates. In a PC, the more frequent level on one attribute appears contingent on the more frequent level on another attribute. When PCs are manipulated orthogonally to conditional probabilities, the former dominate the latter (Fiedler, 2010). PC dominance is shown in Experiments 1 and 1a to be particularly striking when a multivariate task setting calls for the assessment of all k<middle dot>(k - 1)/2 pairwise contingencies between k attributes. Experiment 2 shows that contingency judgments are dissociated from evaluative conditioning.
Gesehen am 27.02.2025